Implications of Integrated Administrative Services (PATEN) Policy on Accountability and Public Satisfaction - Noor, Arifin; Hayati, Rahmi; Halim, Peter; Wibowo, Wahyu (stiatabalong.ac.id, 2026)
The implementation of the Integrated Administrative Services at the Sub-District Level (PATEN) represents a paradigmatic transformation in the delivery of public services oriented towards enhancing accountability and public satisfaction. This study analyses the implications of the PATEN policy on strengthening public service accountability mechanisms and its impact on the level of satisfaction among service users. The research methodology uses a qualitative approach with a literature study technique that analyses academic literature from the period 2021-2025. The results show that the implementation of PATEN contributes significantly to strengthening accountability through procedural transparency, service standardisation, and an integrated monitoring system. The impact on public satisfaction is manifested in increased service accessibility, responsiveness of officials, and elimination of bureaucratic complexity. Determinants of success include human resource capacity, technological infrastructure, leadership commitment, and contextual adaptability. Implementation challenges include resource constraints, resistance to change, and the digital divide. The study concludes that PATEN has strategic potential in realising good governance through quality and responsive public services.